Seasonal droughts during the Miocene drove the evolution of Capparaceae towards Neotropical seasonally dry forests - Mercado-Gómez, Jorge D. (2022)
Introduction: Neotropical seasonally dry forest (NSDF) climatic constraintsincreased endemism, and phylogenetic niche conservatism in species that are restricted to thisbiome. NSDF have a large number of endemic Capparaceae taxa, but it is unknown ifphylogenetic niche conservatism has played a role in this pattern. Objective: We carried out anevolutionary analysis of the climatic niche of neotropical species of Capparaceae to identifywhether the climatic constraints of NSDF have played a major role throughout the family’sevolutionary history. Methods: Using three chloroplastic (ndhF, matK, rbcL) and one ribosomal(rsp3) DNA sequences, we proposed a date phylogeny to reconstruct the evolutionary climaticniche dynamics of 24 Neotropical species of Capparaceae. We tested the relationship betweenniche dissimilarity and phylogenetic distance between species using the Mantel test. Likewise,we used a set of phylogenetic comparative methods (PGLS) on the phylogeny of Capparaceae toreconstruct the main evolutionary historic events in their niche. Results: Capparaceae originatedin humid regions and subsequently, convergent evolution occurred towards humid and dry forestduring the aridification phases of the Middle Miocene (16-11 Mya). However, adaptationtowards drought stress was reflected only during the precipitation of the coldest quarter, wherewe found phylogenetic signal (Pagel ) for gradual evolution and, therefore, evidence ofphylogenetic niche conservatism. We found convergent species-specific adaptations to bothdrought stress and rainfall during the Miocene, suggesting a non-phylogenetic structure in mostclimatic variables. Conclusions: Our study shows how the Miocene climate may haveinfluenced the Capparaceae speciation toward driest environments. Further, highlights thecomplexity of climatic niche dynamics in this family, and therefore more detailed analyses arenecessary in order to better understand the NSDF climatic constrictions affected the evolution ofCapparaceae.